Preventing renal and cardiovascular risk by renal function assessment: insights from a cross-sectional study in low-income countries and the USA. Issue 5 (22nd September 2012) - Cravedi, Paolo; Sharma, Sanjib Kumar; Bravo, Rodolfo Flores; Islam, Nazmul; Tchokhonelidze, Irma; Ghimire, Madhav; Pahari, Bishnu; Thapa, Sanjeev; Basnet, Anil; Tataradze, Avtandil; Tinatin, Davitaia; Beglarishvili, Lela; et al.
Abstract : Objective: To assess the prevalence of microalbuminuria and kidney dysfunction in low-income countries and in the USA. Design: Cross-sectional study of screening programmes in five countries. Setting: Screening programmes in Nepal, Bolivia, the USA (National Health and Nutrition Examination Survey (NHANES) 2005–2008) Bangladesh and Georgia. Participants: General population in Nepal (n=20 811), Bolivia (n=3436) and in the USA (n=4299) and high-risk subjects in Bangladesh (n=1518) and Georgia (n=1549). Primary and secondary outcome measures: Estimated glomerular filtration rate (eGFR)<60ml/min/1.73 m 2 and microalbuminuria (defined as urinary albumin creatinine ratio values of 30–300 mg/g) were the main outcome measures. The cardiovascular (CV) risk was also evaluated on the basis of demographic, clinical and blood data. Results: The prevalence of eGFR<60ml/min/1.73 m 2 was 19%, 3.2% and 7% in Nepal, Bolivia and the USA, respectively. In Nepal, 7% of subjects were microalbuminuric compared to 8.6% in the USA. The prevalence of participants with predicted 10-year CV disease (CVD) risk ≥10% was 16.9%, 9.4% and 17% in Nepal, Bolivia and in the USA, respectively. In Bangladesh and Georgia, subjects with eGFR<60 ml/min/1.73 m 2 were 8.6% and 4.9%, whereas those with microalbuminuria were 45.4% and 56.5%, respectively. Predicted 10-year CVD risk ≥10% was 25.4% and 25% in Bangladesh and Georgia, respectively. Conclusions: Renal abnormalities are common among low-income countries and in the USA. Prevention programmes, particularly focused on those with renal abnormalities, should be established worldwide to prevent CVD and progression to end-stage renal disease.